Pengaruh Total Asset Turnover (TATO) dan Leverage Terhadap Nilai Perusahaan pada PT Waskita Karya (Persero) Tbk - Putriani Putriani; Aliah Pratiwi; M. Rimawan (Lembaga Intelektual Muda (LIM) Maluku, 2026)
This study aims to analyze the effect of Total Asset Turnover (TATO) and Leverage, proxied by Debt to Equity Ratio (DER), on firm value at PT Waskita Karya (Persero) Tbk during the 2015–2024 period. Firm value was measured using Tobin’s Q ratio. This research employed a quantitative approach with an associative method. The data used were secondary data obtained from the company's annual financial statements. Data analysis techniques included classical assumption tests, multiple linear regression analysis, correlation coefficient, coefficient of determination, t-test, and F-test using SPSS software. The results indicate that partially, Total Asset Turnover (TATO) has no significant effect on firm value with a significance value of 0.639 > 0.05. Debt to Equity Ratio (DER) also has no significant effect on firm value with a significance value of 0.514 > 0.05. Simultaneously, TATO and DER do not significantly affect firm value with a significance value of 0.780 > 0.05. These findings suggest that asset utilization efficiency and capital structure have not been the primary factors influencing the firm value of PT Waskita Karya (Persero) Tbk during the study period.